Hubungan Antara Dukungan Keluarga Dan Kualitas Hidup Pasien Skizofrenia di Layanan Keperawatan Komuniats: Tinjauan Pustaka - Rahma Raisa Nurfauzia; Lilis Lismayanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Schizophrenia is a severe mental illness that impairs cognitive, emotional, and social functioning, reducing quality of life. The aim of this study was to examine how family dynamics and quality of life are related to individuals with schizophrenia receiving community support services. The methodology used was a systematic literature review in accordance with PRISMA guidelines, which included three quantitative cross-sectional studies that observed the relationship between family dynamics and quality of life using standardized criteria (WHOQOL-BREF). The analysis revealed a significant correlation between family environment and patient quality of life (p < 0.05), with moderate to strong correlations. Therefore, family support, especially emotional, informational, and practical support, is crucial for improving the quality of life and well-being of patients with schizophrenia. Therefore, family-oriented interventions in community-based services need to be strengthened